2016
DOI: 10.1007/s11356-016-7172-5
|View full text |Cite
|
Sign up to set email alerts
|

Levels, sources, and health risk assessment of polycyclic aromatic hydrocarbons in Brno, Czech Republic: a 5-year study

Abstract: This work aimed to determine the seasonal variations of polycyclic aromatic hydrocarbons (PAHs) in airborne PM at two background sites (Masná-MS, Líšeň-LN) in Brno over a 5-year period (2009-2013). Samples were collected on quartz filters using a low-volume sampler by continual filtration. Concentrations of PAHs in collected PM samples were determined using a gas chromatography with a mass spectrometer as a detector. A different number of PAHs were determined to be at each site, i.e., 11 PAHs at the MS site an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…The higher CDI levels in colder season compared to warmer season observed in this study is in agreement with those reported in the literature (Amarillo et al, 2017;Bulejko et al, 2016;Ugranli et al, 2016). The mean inhalation risk level for Σ 15 PAHs were estimated below 10 − 6 in all seasons, except in winter (1.65 × 10 −6 ).…”
Section: Population Exposure and Carcinogenic Riskssupporting
confidence: 92%
“…The higher CDI levels in colder season compared to warmer season observed in this study is in agreement with those reported in the literature (Amarillo et al, 2017;Bulejko et al, 2016;Ugranli et al, 2016). The mean inhalation risk level for Σ 15 PAHs were estimated below 10 − 6 in all seasons, except in winter (1.65 × 10 −6 ).…”
Section: Population Exposure and Carcinogenic Riskssupporting
confidence: 92%
“…Significant success in preventing the infection, has been achieved by decreasing the amount of some air contaminants such as dust, allergens, microorganisms, welding fumes and combustion-generated particles utilizing air filtration. It has been found that there is a direct association between high concentrations of airborne particles and human health disorders ( Bulejko et al, 2016 ). Nowadays the mask's filter is constructed from layers of cotton gauze to prevent people from the aerosols.…”
Section: Environment and Virus Transmission Ratementioning
confidence: 99%
“…The selected principal components have cumulative variances that exceed 85% of the total variance after the application of the varimax rotation. These factors could be considered in order to reflect the specific chemical sources of target pollutants [25,26]. The Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model is one of the most extensively used atmospheric transport and dispersion models in the atmospheric sciences community [6,27,28].…”
Section: Source Apportionment Techniques Of Pahsmentioning
confidence: 99%